Formation and Sustainability in Historical Squares: An Analysis on The Example of Nicosia Historical Urban Texture - Turkan, Zihni (European Journal of Sustainable Development, 2024)
Squares, which are social meeting and community areas of societies, have shaped important public open spaces of settlements. Located in historical urban textures, such spaces are also a source reflecting the history of the city with the artefacts from their formation processes. The squares acquired their identity through surrounding formations from different periods in the history of Cyprus and have come to the present day with their active lives. Saray